Factors Associated With Cancer Patients’ Preferences for Telemedicine or In-Person Palliative Care - Kim, Min Ji; Tang, Michael; Taylor, Terry; Chen, Minxing; Hui, David; Reddy, Akhila; Narayanan, Santhosshi; Bruera, Eduardo (Journal of pain and symptom management, 2025)
Prior studies demonstrate sociodemographic factors as barriers to telemedicine. Greater understanding of telemedicine preferences in cancer patients receiving palliative care and factors associated with their preferences could inform future care delivery in this vulnerable population. This study aimed to identify cancer patients’ preferences for in-person vs. telemedicine palliative care visits in real-world clinical practice and associated patient-centric factors. This was a retrospective study involving chart review of in-person or telemedicine palliative care visits between September 2021 and October 2021, during which patients’ preferences for telemedicine or in-person visits and perceived difficulty coming in-person were routinely asked. Their answers were collected from the electronic chart. Associations between visit preference and sociodemographic and clinical factors were identified. Of 400 patients, mean age was 59 years. 217 (54%) were female. 285 (71%) were White. Most had advanced cancer (344; 86%). 83% (n = 333) preferred telemedicine. 72% (n = 288) cited difficulty coming in-person. On univariate analysis, female gender (P = 0.03), college completion (P < 0.01), and perceived difficulty coming in-person (P < 0.01) were associated with preferring telemedicine. Positive Cut-Down, Annoyed, Guilty, Eye-Opener-Adapted to Include Drugs (CAGE-AID) score (P = 0.02) was associated with in-person preference. On multivariate analyses, perceived difficulty coming in-person was associated with telemedicine preference (OR: 16.81; 95% CI: 7.91–35.28; P < 0.01). A positive CAGE-AID score was associated with in-person preference (OR: 0.17; 95% CI: 0.05–0.59; P = 0.01). Most patients having outpatient palliative care visits preferred telemedicine. Perceived difficulty coming in-person was associated with telemedicine preference. Patients with positive CAGE-AID scores were less likely to prefer telemedicine.